Evaluation of a hulled wheat (emmer and spelt) collections - Quaranta F.; Belocchi A.; Camerini M.; Cecchini C.; Fornara M.; Pucciarmati S.; D'Egidio M.G. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
A collection of 422 accessions of hulled wheat (219 emmer and 203 spelt) was studied to individuate the variability for some morphological and qualitative traits (heading date, plant height, thousand kernel weight, grain protein content, SDS sedimentation test). Results of this work highlighted a huge variability for the examined traits both for emmer and spelt accessions. Several accessions, possessing useful agronomical traits like earliness, short straw, large kernel, high protein content and SDS values, were identified for further evaluation in replicated trials.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)